Development of a comprehensive dashboard for academic management in higher learning institution - Chow, Wai Kean (2023)
As the number of students pursuing higher education continues to grow, decisionmaking for university stakeholders gets more challenging. This project aims to develop a performance dashboard that allows educators and management to monitor and analyse the academic progress and achievements of students from a diverse background and intake. Targeted users of this dashboard are internal users involved actively in formulating strategic business decisions and interested in analysing the pattern or trend of the program. The research methodology used in this project is a modified Knowledge Discovery in Databases (KDD) to achieve the project objective. The steps include domain understanding, data pre-processing, feature engineering, dashboarding, and evaluation. The project had successfully developed comprehensive dashboard to monitor student performance. System usability scale results had indicated that the dashboard developed is user friendly and users agreed that the dashboard able to provide insight for decision making based on student performance.